2021
DOI: 10.1029/2020gl092281
|View full text |Cite
|
Sign up to set email alerts
|

Present and Future of Rainfall in Antarctica

Abstract: During the austral summer 2013-2014, an Adélie penguin colony near Dumont d'Urville (DDU) station, coastal Adélie Land, Antarctica, experienced a complete reproductive failure, a so-called "zero" year. Among the main reasons for this disaster was an unusual and dramatic rainfall event that occurred on January 1, 2014, and that was responsible for the death of all chicks, whose downy plumage has little waterproofing ability (Ropert-Coudert et al., 2015). According to ice-core records in which water from rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 74 publications
(70 reference statements)
2
31
0
Order By: Relevance
“…This is especially relevant in polar environments, even though rainfall occurrence is predicted to increase in the coming decades. 76 The metaanalysis performed here allows for calculating the ratio between K RG versus de K SA (the snow-air partition coefficient) from the field-derived data. For such a comparison, we use K SA as estimated in a companion meta-analysis reported elsewhere.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially relevant in polar environments, even though rainfall occurrence is predicted to increase in the coming decades. 76 The metaanalysis performed here allows for calculating the ratio between K RG versus de K SA (the snow-air partition coefficient) from the field-derived data. For such a comparison, we use K SA as estimated in a companion meta-analysis reported elsewhere.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These two islands are located in the South Shetland Archipelago (Figure S1) in the Antarctic Peninsula. In this area, periods with temperatures above freezing during summer allow rain to fall . The samples for PFAS analysis were collected in both islands; however, the samples for OPEs and PAHs were collected only in Livingston Island.…”
Section: Methodsmentioning
confidence: 99%
“…Third, related with melt water, rainfall events lead to periods of extremely high rates of rn saturation and runoff 30 . Runoff here refers to liquid water beyond the saturation point of the snowpack that does not necessarily drain into the ocean and could remain on the ice shelf.…”
Section: Ice Shelf Calving and Collapse Cooccurrences With Arsmentioning
confidence: 99%
“…A recent study by Vignon et al (2021) showed that a significant portion of the annual precipitation on the western AP occurs as rainfall. The chances of rain and associated surface melt in West Antarctica and the AP increase markedly during warm air intrusions and atmospheric rivers (Wille et al, 2019;Nicolas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The chances of rain and associated surface melt in West Antarctica and the AP increase markedly during warm air intrusions and atmospheric rivers (Wille et al, 2019;Nicolas et al, 2017). Recent studies of precipitation projections show increases in consecutive wet days (Chyhareva et al, 2019) and rain and melt days (Bozkurt et al, 2021;Vignon et al, 2021) in the AP region during the 21 st century, indirectly indicating that surface melt will continue.…”
Section: Introductionmentioning
confidence: 99%